Experimental warming reduced topsoil carbon content and increased soil bacterial diversity in a subtropical planted forest. (June 2019) - Wang, Hui; Liu, Shirong; Schindlbacher, Andreas; Wang, Jingxin; Yang, Yujing; Song, Zhanchao; You, Yeming; Shi, Zuomin; Li, Zhaoying; Chen, Lin; Ming, Angang; Lu, Lihua; et al.
Abstract: The potential effects of global warming on the soil carbon (C) dynamics of subtropical forests are uncertain. To assess the effects of warming on soil C and tree roots, combined soil warming (infrared heaters, +1.5 °C soil temperature) and trenching experiments were conducted in a subtropical Castanopsis hystrix plantation. Topsoil C content was reassessed after five years of warming, and the effects on soil organic carbon (SOC) quality and microbial diversity were analyzed. Compared with corresponding controls, the topsoil (0–10 cm) SOC content was significantly lower in un-trenched warmed soil (−13.6%) as well as in trenched warmed soil (−15.4%). However, the range of SOC content after five years of warming was similar to that observed after two years of warming (−14.6%, −19.2%), indicating that the warming effect on SOC content had leveled off during the latter three years of the study. In trenched plots, warming significantly decreased the carbohydrate C as well as the ratio of carbohydrate C to N-alkyl/methoxyl C (CC/MC), suggesting that labile C was preferentially decomposed. In un-trenched plots, SOC quality was unaffected, indicating a compensatory input of labile root C. Bacterial α-diversity increased under warming, whereas no significant warming effects on fungal community diversity were observed. Both the SOC content and the proportion of soil carbohydrate C were negatively correlated with soil bacterial α-diversity, suggesting that the abundance of more recalcitrant SOC increased soil microbial diversity. Overall, our study indicates that soil warming leads to moderate initial reductions in topsoil SOC in the studied forest ecosystem. This is consistent with recent evidence that low SOC-containing soils (e.g., subtropical forest soils) exhibit a weaker response to soil warming than high SOC-containing soils. Highlights: After five years of warming, SOC content was significantly lower in warmed soils. Reduction in SOC content was in a range similar to that after two years of warming. Warming decreased carbohydrate C, and carbohydrate C to N-alkyl/methoxyl C ratio. SOC content and quality were negatively correlated with soil bacterial α-diversity.